2019
DOI: 10.1002/cssc.201900730
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic CO2 Reduction with a Ruthenium Catalyst in Solution and on Nanocrystalline TiO2

Abstract: A RuII complex [Ru(PO3Et2‐ph‐tpy)(6‐mbpy)(NCCH3)]2+ [PO3Et2‐ph‐tpy=diethyl(4‐[(2,2′:6′,2′′‐terpyridin)‐4′‐yl]phenyl)phosphonate; 6‐mbpy=6‐methyl‐2,2′‐bipyridine] is explored as a molecular catalyst for electrocatalytic CO2 reduction in both a homogeneous solution and, as a phosphonated derivative, on nanocrystalline‐TiO2 surfaces. In CH3CN, the complex acts as a selective electrocatalyst for reduction of CO2 to CO at a low overpotential of 340 mV but with a limited turnover number (TON). An enhancement in reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…TOF was determined using equation from catalytic CVs: TOF=italicFvnp3RT0.4463ncat2icatinormalp2 where F is Faraday's constant (96485 C/mol), v is the scan rate employed (0.1 V/s), n p is the number of electrons involved in the non‐catalytic redox reaction ( n p = 1), R is the gas constant (8.314 J/K/mol), T is the temperature (293.15 K), and n cat is the number of electrons involved for the catalytic reaction ( n cat = 2 for the reduction of CO 2 to CO), i p and i cat are determined as the peak currents under Ar and CO 2 , respectively. As for complex 1 , the calculated TOF is 4.4 s −1 ( i cat / i p = 4.7) in MeCN solution at a potential of −1.85 V, which is higher than or comparable to that of many reported ruthenium molecular water oxidation catalysts, and 0.4 s −1 ( i cat / i p = 1.5) in THF solution at a potential of −1.94 V and a scan rate of 100 mV/s. As for complex 2 , the calculated TOFs are 0.3 s −1 ( i cat / i p = 1.2) in MeCN solution at a potential of −2.43 V and 0.2 s −1 ( i cat / i p = 0.9) in THF solution at a potential of −2.21 V at 100 mV/s.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…TOF was determined using equation from catalytic CVs: TOF=italicFvnp3RT0.4463ncat2icatinormalp2 where F is Faraday's constant (96485 C/mol), v is the scan rate employed (0.1 V/s), n p is the number of electrons involved in the non‐catalytic redox reaction ( n p = 1), R is the gas constant (8.314 J/K/mol), T is the temperature (293.15 K), and n cat is the number of electrons involved for the catalytic reaction ( n cat = 2 for the reduction of CO 2 to CO), i p and i cat are determined as the peak currents under Ar and CO 2 , respectively. As for complex 1 , the calculated TOF is 4.4 s −1 ( i cat / i p = 4.7) in MeCN solution at a potential of −1.85 V, which is higher than or comparable to that of many reported ruthenium molecular water oxidation catalysts, and 0.4 s −1 ( i cat / i p = 1.5) in THF solution at a potential of −1.94 V and a scan rate of 100 mV/s. As for complex 2 , the calculated TOFs are 0.3 s −1 ( i cat / i p = 1.2) in MeCN solution at a potential of −2.43 V and 0.2 s −1 ( i cat / i p = 0.9) in THF solution at a potential of −2.21 V at 100 mV/s.…”
Section: Resultsmentioning
confidence: 53%
“…Molecular catalysts based on ruthenium transition metal complexes for electrochemical reduction of CO 2 have attracted considerable research attention due to their unique structural and electronic features, as well as, homogeneous complexes retaining the advantages of elucidating catalytic processes for optimizing the catalysts . A great many remarkable achievements have been reported by Meyer, Kubiak, Tanaka, Fujita, Miller, Huang, and others …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several tpy-Ru complexes have proven to be active catalysts towards CO2 reduction, [28][29][30][31][32] therefore NiO photocathodes, coated with the HOOC-(Zn)DMP-tpy-Ru dyad, were used as working electrodes for the fabrication of DSPECs. The reaction medium was a mixture of acetonitrile/water in a 9/1 ratio with Bu4NPF6 as supporting electrolyte.…”
Section: Photocatalytic Testsmentioning
confidence: 99%
“…Finally, Meyer and co-workers, along with other groups, have demonstrated that tpy-Ru derivatives can work as catalysts for either alcohol oxidation [23][24][25][26][27] and/or for CO2 reduction. [28][29][30][31][32] Consequently, the dyads containing the tpy-Ru unit could be implemented in DSPECs as photocatalysts for either alcohol oxidation on TiO2 or CO2 reduction on NiO. Alcohol oxidation seems to be more appealing than water oxidation into oxygen, because the latter requires four holes to operate instead of only two that are needed for alcohol oxidation and necessitates a higher potential (1.23 V vs. NHE for water versus -0.143 V vs. NHE for benzyl alcohol oxidation).…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) has been widely used as a model catalyst material in various areas such as photo and thermal catalytic applications for energy and environment [1][2][3][4][5][6]. To satisfy increasing demand, considerable effort has been devoted to the designing of new catalysts with higher catalytic performance [1,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%